Analysis of reinforced concrete beams with web openings [electronic resource] - 172974 Toh, Yik Fung; Fakulti Kejuruteraan Awam (2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005